Financial Deepening Elasticity Of Macroeconomic Variables In Indonesia - Moch. Syamsudin (IJED: International Journal of Economy Development Research, 2026)
Financial deepening is an effort made in the financial sector to increase domestic savings and reduce dependence on foreign savings. Increasing the amount of financial volume at financial institutions and improving the quality of financial services. The elasticity that occurs in financial deepening is caused by the money supply, total credit and total savings that affect the state of economic growth in Indonesia. The method used is vector error correction model (VECM). The results show that the elasticity of financial deepening has an effect on economic growth in Indonesia both in the short and long term. External economic shocks and uncertainties in the world economy have an impact on financial deepening and economic growth. The results of forecasting on the variables of economic growth and financial deepening show that economic growth and an increase in the money supply have increased but total savings have decreased significantly. These results recommend that prudent monetary policy and prudence are needed in determining the size of the interest rate instrument. The actualization of the central bank's policy in regulating financial deepening has contributed greatly to the creation of a stable economy.